If it's not what You are looking for type in the equation solver your own equation and let us solve it.
11-x=3x+11
We move all terms to the left:
11-x-(3x+11)=0
We add all the numbers together, and all the variables
-1x-(3x+11)+11=0
We get rid of parentheses
-1x-3x-11+11=0
We add all the numbers together, and all the variables
-4x=0
x=0/-4
x=0
| 4=u+6÷3 | | 2=2y-(2y-2) | | (1+x)/(1+(x*x)=2/5 | | 3(v-9)=3v+27 | | -1-3x=-14+10x | | 2n+n+3(n+4)=8n | | t/7=6/10.5 | | 6*x-6+20=-21 | | x+6(-1)=-7 | | 6x-44=4(x-6) | | 3^9x=27 | | 8m-7=6m+3 | | -6-6x=36 | | 15j+4j-18j=3 | | 2x-7=11x+8 | | -12=p-5-5 | | 2+3x=5+9x | | 2-r=13 | | 6(u-2)-8u=-30 | | 6*x-6+20=21 | | 5g+4(-6+4g)=1−g | | -14=-2/9y | | 6(u-2)8u=-30 | | 8f-6=6f | | 15=3(h-11) | | 220=-4x+7(6x-12) | | 6•x-6+20=21 | | (1+x)/(1+(x*x)=3/5 | | 3+2(m+3)=2(2m+1) | | 5g+4(-6+4g)=11−g | | 5=4d=-13-2d | | 18=3-5(x+2) |